2021
DOI: 10.3390/ijms22189953
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of the Gas6/Axl Signaling Pathway in Cancer

Abstract: Many signaling pathways are dysregulated in cancer cells and the host tumor microenvironment. Aberrant receptor tyrosine kinase (RTK) pathways promote cancer development, progression, and metastasis. Hence, numerous therapeutic interventions targeting RTKs have been actively pursued. Axl is an RTK that belongs to the Tyro3, Axl, MerTK (TAM) subfamily. Axl binds to a high affinity ligand growth arrest specific 6 (Gas6) that belongs to the vitamin K-dependent family of proteins. The Gas6/Axl signaling pathway ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 166 publications
1
33
0
Order By: Relevance
“…It was observed that Gas6 is frequently overexpressed in lung cancer cells and is found in the plasma [ 42 , 43 ], and Gas6 is associated with cell growth of stromal cancerous cells and tumor progression [ 44 ]. Therapeutic agents targeting Gas6 and AXL have been developed, and promising results have been observed in both preclinical and clinical settings when such agents are used alone or in combination [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that Gas6 is frequently overexpressed in lung cancer cells and is found in the plasma [ 42 , 43 ], and Gas6 is associated with cell growth of stromal cancerous cells and tumor progression [ 44 ]. Therapeutic agents targeting Gas6 and AXL have been developed, and promising results have been observed in both preclinical and clinical settings when such agents are used alone or in combination [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Important tyrosine residues in the intracellular domain include the activation loop (Tyr698, Tyr702, Tyr703) and the C-terminal domain (Tyr779, Tyr821, Tyr866), which are necessary for the recruitment of adaptor proteins mediating signaling cascades including the adaptor GRB2 leading to the activation of phosphatidylinositol 3 kinase (PI3K), phospholipase C (PLC), or SRC kinase. In a cell type- and tissue-dependent context, it triggers the downstream activation of various signaling pathways, including PI3K-AKT, NF-KappaB; RAS-MEK-ERK, JAK-STAT, SRC/FAK ( 6 , 7 , 21 , 22 , 36 38 ). In addition to the canonical GAS6/AXL activation pathway, evidence is accumulating that malignant cells have developed various ways to bypass, at least in part, their dependence on GAS6 ( 21 , 39 41 ).…”
Section: The Biology Of Tams and Gas6/axl Signalingmentioning
confidence: 99%
“…Due to the pro-tumoral, pro-metastatic, and treatment resistance roles of AXL, numerous therapeutic interventions targeting AXL have been designed and investigated. Several investigators have covered this topic well to which the readers can be referred ( 7 , 21 , 22 , 30 , 36 38 , 53 , 119 , 172 , 195 ).…”
Section: Toward Standardization Of Axl-targeting Agents In Combinatio...mentioning
confidence: 99%
“…Among the three receptors, Axl has the highest affinity for GAS6 (Tanaka & Siemann, 2021). Multiple studies focused on GAS6/Axl signaling in the progression and metastasis of cancer (Tanaka & Siemann, 2021). Furthermore, the role of the GAS6/Axl pathway in organ protection, especially brain, under various pathological progresses has also been widely investigated (Ray et al, 2017; Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Growth arrest-specific gene 6 (GAS6), discovered in 1988, is a Vitamin K-dependent protein and participates in immune regulation and inflammation by binding to the TAM receptor (Tyro3, Axl, and Mer). Among the three receptors, Axl has the highest affinity for GAS6 (Tanaka & Siemann, 2021). Multiple studies focused on GAS6/Axl signaling in the progression and metastasis of cancer (Tanaka & Siemann, 2021).…”
mentioning
confidence: 99%